Health-Promoting Family Approach (1972-2024): A Bibliometric Study - Febryanti, Ade; Yulianti, Risda; Pravita Sari , Ayu (International Journal of Medical Science and Clinical Research Studies, 2024)
Background: The Health Promoting Family Approach involves a comprehensive perspective that extends beyond the conventional medical approach. It recognizes the intricate relationships among family dynamics, social and cultural backgrounds, and health habits. In this approach, families are seen not just as passive participants in health initiatives, but as influential contributors who play a pivotal role in molding health behaviors, mindsets, and ways of life. Material/Method: The research methodology involved descriptive bibliometric analysis using data gathered from international publications sourced from the Scopus database (accessible in www.scopus.com). The analysis was conducted using VOSViewer version 1.6.18 and R-Studio version 4.3.2, facilitating bibliometric analysis. Information regarding the study, focusing on the "health promoting family approach" keyword. Result: The results of bibliometric analysis show that publication trends from 1972 to 2024 have increased. Some of the most frequently used keywords by the authors include: human, female, male, health promotion, public health, family, qualitative research, mental health, and health. The journal BMC Public Health publishes the most articles about the Health Promoting Family Approach, with a total of 49 articles. The highest number of writer collaborations is from the United States. And the paper by Lobstein is the most globally cited document with a total of 3022 citations. Conclusion: Trend in publications on the Health-Promoting Family Approach, particularly concerning mental health, from 1972 to 2024, has shown an increasing trajectory, indicating a growing interest and relevance in this topic. Authors from developed countries such as the USA and the United Kingdom have contributed the most to these publications.